Microstrip Triplexer Design: A Review - Shairi, Noor Azwan; Sazali, M.A.; Zakaria, Zahriladha (Penerbit Universiti, UTeM, 2017)
Radio Frequency communication systems were developed in the past decades and many designs are involved in triplexer development. The previous designs focused on various purposes, new techniques, and applications in order to overcome the existing limitations. This manuscript presents several reviews for the past triplexer designs and techniques used in RF communication systems in order to propose a novel design and an improvement concept, and reduce limitation gaps of triplexer design for future research work.